Utilizing Household Organic Waste into Eco-Enzyme: A Community Environmental Education and Action Program - Sutiharni, Sutiharni; Mariay, Ivonne Fitri; Andriyani, Liz Yanti (Journal Ligundi of Community Service, 2025)
Background. The rapid increase in household organic waste generation poses serious environmental and health challenges in urban and rural communities. Improper disposal methods, such as open dumping and uncontrolled decomposition, contribute to greenhouse gas emissions and water contamination. Eco-enzyme, a natural bio-solution produced from fermenting organic waste such as fruit peels and vegetable scraps with brown sugar and water, has emerged as an eco-friendly innovation to address this issue. This environmentally sustainable approach not only minimizes waste but also produces multipurpose organic enzymes useful for cleaning, agriculture, and wastewater treatment. Purpose. This study aims to explore the utilization of household organic waste in producing eco-enzyme as a form of community-based environmental empowerment. The research seeks to examine the effectiveness of eco-enzyme production in reducing household waste volume and promoting environmental awareness among local residents. Method. T The study employed a mixed-method approach combining quantitative measurement of waste reduction and qualitative observation of community participation. Data were collected through surveys, waste audits, and focus group discussions within a pilot community program involving 50 households over three months. The fermentation process followed a standardized 3:1:10 ratio of waste, brown sugar, and water, respectively, and outcomes were analyzed for both environmental and social impacts. Results. Findings revealed a 45% reduction in organic waste volume and a significant increase in residents’ environmental literacy. Eco-enzyme products demonstrated practical effectiveness in cleaning and soil enrichment. Conclusion. The study highlights eco-enzyme utilization as an accessible, low-cost, and sustainable strategy for community waste management. It reinforces the role of participatory environmental education in cultivating ecological responsibility and supports the transition toward circular economy practices at the grassroots level.